Completeness and timeliness of Salmonella notifications in Ireland in 2008: a cross sectional study - Cormican Martin; Delappe Niall; Garvey Patricia; Nicolay Nathalie; McKeown Paul (BMC, 2010)
Abstract Background In Ireland, salmonellosis is the second most common cause of bacterial gastroenteritis. A new electronic system for reporting (Computerised Infectious Disease Reporting - CIDR) of Salmonella cases was established in 2004. It collates clinical (and/or laboratory) data on confirmed and probable Salmonella cases. The authors studied the completeness and the timeliness of Salmonella notifications in 2008. Methods This analysis was based upon laboratory confirmed cases of salmonella gastroenteritis. Using data contained in CIDR, we examined completeness for certain non-mandatory fields (country of infection, date of onset of illness, organism, outcome, patient type, and ethnicity). We matched the CIDR data with the dataset provided by the national Salmonella reference laboratory (NSRL) to which all Salmonella spp. isolates are referred for definitive typing. We calculated the main median time intervals in the flow of events of the notification process. Results In total, 416 laboratory confirmed Salmonella cases were captured by the national surveillance system and the NSRL and were included in the analysis. Completeness of non mandatory fields varied considerably. Organism was the most complete field (98.8%), ethnicity the least (11%). The median time interval between sample collection (first contact of the patient with the healthcare professional) to the first notification to the regional Department of Public Health (either a clinical or a laboratory notification) was 6 days (Interquartile 4-7 days). The median total identification time interval, time between sample collections to availability of serotyping and phage-typing results on the system was 25 days (Interquartile 19-32 days). Timeliness varied with respect to Salmonella species. Clinical notifications occurred more rapidly than laboratory notifications. Conclusions Further feedback and education should be given to health care professionals to improve completeness of reporting of non-mandatory fields. The efficiency of reporting was similar to that published elsewhere. Delays in the reporting system at present mean that although the system is of value in facilitating comprehensive reporting it is unlikely it can be relied upon for rapid detection of outbreaks at an early stage. Direct person-to-person, communication between clinical and reference laboratories and public health practitioners remains a critical element of the surveillance system for rapid outbreak detection.